1991
DOI: 10.1002/art.1780340706
|View full text |Cite
|
Sign up to set email alerts
|

Serum hyaluronate level as a predictor of radiologic progression in early rheumatoid arthritis

Abstract: PATIENTS AND METHODSRA patients. Forty consecutive patients (31 women, 9 men) with newly diagnosed definite or classic RA (according to the 1958 criteria of the American Rheumatism Association [9]) were included in the study. The mean duration of disease in the RA patients at the beginning of the study was 7.0 months (range 2-12 months). The mean age of the patients was 41.5 years (range 19-61). At the time of diagnosis, 27 of the patients (67.5%, 18 women and 9 men) were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 25 publications
3
26
1
2
Order By: Relevance
“…8 Other studies found a lower rate of erosiveness than our study (67% v 37% 9 and 29% 10 ) in patients with a longer period of evolution-that is <12 9 or <24 10 months. There may be several reasons for these different results.…”
Section: Discussioncontrasting
confidence: 53%
“…8 Other studies found a lower rate of erosiveness than our study (67% v 37% 9 and 29% 10 ) in patients with a longer period of evolution-that is <12 9 or <24 10 months. There may be several reasons for these different results.…”
Section: Discussioncontrasting
confidence: 53%
“…In conclusion, levels of serum HA, which are thought to be a marker of synovial inflammation (21,22) and have been shown to correlate with ongoing joint damage in RA (23), also predict disease progression in established tibiofemoral OA, a disease in which systemic markers of inflammation are usually within the normal range. The only other serum measure that has been reported to be of prognostic significance in OA is insulin-like growth factor 1 (24).…”
Section: Discussionmentioning
confidence: 92%
“…Another parameter which also correlated with the increase of serum HYA levels was the Ritchie index, indicating that the serum HYA level provides a measure of synovitis mass [12]. Of clinical importance was the observation that high serum HYA levels early in the disease indicate a more aggressive course with progressive erosion [13].…”
Section: Serum Analysis In Rheumatic Diseasesmentioning
confidence: 99%